Analysis of camphorquinone in composite resins as a function of shade - Alvim, Hugo H.; Alecio, Alberto C.; Vasconcellos, Walison A.; Furlan, Maysa [UNESP]; Oliveira, Jose Eduardo de [UNESP]; Saad, Jose R. C. (Elsevier B.V., 2007)
Objective. To identify and quantify the camphorquinone (CQ) used in different brands of composite resins as a function of the shade analyzed.Materials and methods. Filtek Z250 A3 (FZA3), Filtek Z-250 Incisal (FZI), Pyramid Enamel A1 (PEA1), Pyramid Enamel Translucent (PET), Filtek Supreme A3E (FSA3) and Filtek Supreme GT (FSGT) were used. Five hundred milligrams of each resin were weighed and then dissolved in 1.0 ml of methanol. The samples were centrifuged to accelerate the sedimentation of the inorganic particles. 0.8 ml of the supernatant solution was collected with a pipette and assessed under gas chromatography coupled to the mass spectrometer (GC-MS). The results were compared to pure CQ solutions, used as a standard. Student's t-test, (p = 0.05) significant at the level of 5%, compared the results of each brand shade.Results. A smaller amount of camphorquinone was found in Filtek Z-250 (FZI) resin incisal shade when compared to (FZA3) A3 shade. on the other hand, Filtek Supreme resin featured a statistically larger camphorquinone amount in the incisal shade. in Pyramid Enamel resin camphorquinone was found only in shade Al, while the photoinitiator used in the Translucent shade was not identified.Significance. Based on the data obtained, it is possible to conclude that a single composite resin brand may feature differences in amount and type of photoinitiator used. (C) 2006 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: composite resins; gas chromatography; polymers; spectrum analysis; photoinitiator; shade